Association of end‐stage renal disease with HLA phenotypes and panel reactive antibodies in patients awaiting renal transplantation in Hunan Province. Issue 3 (26th January 2022) - Long, Lu; Sun, Qian
Abstract: Objectives: To explore the immune‐related genetic susceptibility of human leukocyte antigen (HLA) alleles and their correlation with panel reactive antibody (PRA) generation during end‐stage renal disease (ESRD) progression. Materials and methods: Data of the expression patterns of HLA‐A, ‐B, and ‐DR alleles and PRAs of 347 ESRD patients awaiting renal transplantation in Hunan Province from 2015 to 2019 were retrospectively studied. The polymerase chain reaction with sequence‐specific primers was used for HLA genotyping and the enzyme‐linked immunosorbent assay for PRA detection. SPSS 21.0 software was used for all allele frequency and statistical analyses. Results: Thirteen HLA‐A, 25 HLA‐B, and 13 HLA‐DR alleles were expressed. The allele frequencies of HLA‐A2, ‐B48, ‐B52, and ‐B55 were significantly higher in the case group than in the control group ( p < 0.05), whereas that of HLA‐B60 was significantly higher in the control group ( p < 0.05). The frequency of HLA alleles in the PRA‐positive group was significantly higher in females than in males ( p < 0.05). The allele frequencies of HLA‐A2, ‐B38, and ‐B46 were significantly higher in the PRA‐positive group than in the PRA‐negative one ( p < 0.05), whereas that of HLA‐60 was significantly higher in the PRA‐negative group ( p < 0.05). Conclusion: HLA‐A2, ‐B48, ‐B52, and ‐B55 may be the ESRD susceptibility alleles in Han Chinese patients in Hunan Province, whereas HLA‐B60 may be the protective allele. Patients carrying HLA‐A2, ‐B38, and ‐B46 are more likely to develop PRA positivity, whereas the opposite is true for those with HLA‐B60. Abstract : Kidney transplantation using organs from relatives or donors is one of the main treatment methods for patients with end‐stage renal disease​(ESRD). The HLA genes, which are highly polymorphic, determine the compatibility of transplanted tissue with the recipient's HLA phenotype. Panel reactive antibodies (PRAs) are anti‐HLA antibodies produced in the serum of patients, and the patient with positive PRA is sensitized and the risk of kidney transplantation failure will be high. HLA‐A2, ‐B48, ‐B52, and ‐B55 may be the ESRD susceptibility alleles in Han Chinese patients in Hunan Province, whereas HLA‐B60 may be the protective allele. Patients carrying HLA‐A2, ‐B38 and ‐B46 are more likely to develop PRA positivity, whereas the opposite is true for those with HLA‐B60.